An exploratory assessment of multistream deep neural network fusion : design and applications - Almeida, Ana Paula Gonçalves Soares de (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2022.